(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This scientific article provides a comprehensive analysis of the application of parametric 3D design technologies in the process of improving outerwear constructions. During the research, key elements of the construction were developed based on digital modeling, and their functional and ergonomic properties were evaluated in a virtual environment. The results show that the parametric 3D design approach ensures higher accuracy, flexibility, and production efficiency compared to traditional design methods.